ANALISIS KIMIA 6 JENIS KAYU UNTUK HUTAN TANAMAN INDUSTRI - Gustan Pari; Nurmala Hudaya (Jurnal Penelitian Hasil Hutan, 1992)
This paper  deals with  a  chemical  analysis  of  six wood  species  obtained   from  industrial plantation Forest. The  analysis  comprises  of  the  determination    of  holocellulose.  lignin, pentosan,  moisture  content,   ash content, silica content  and  solubility  in cold water  hot  water,  sodium  hydroxide and ethanol  benzene   content. The result  shows  that  holocellulose  content  ranges  from  50.2  -   63.2 percent,    cellulose from  42.6  -   56.2 percent. The  high. celloluse content  are Dipterocarpus  haseltii,   Diryobalanops     lanceollata,  Shorea    and Agathis  ]orantifo1ia. Lignin   '(rom  .24. 7  -    3'2.4  percent,    pentosan   from   15.2  -    19.0  percent.   ash cotent  from   0. 4 - 1. 8 percent.   Silica content from 0.1 -    a. 2 percent,   moisture   content from    10.2 -   32.0 percent.   Solubility  in cold water  from  2. 0 - 5.1 percent,    hot  water  from  3.5 -   5.8 percent,  in one percent   sodium  hydroxide  from  12.9 -   17. 6 percent   and so lubility in  ethano1-benzene   (1:2)  from   5.2 - 13.2 percent.Based  on  chemical  analysis, especially  the  cellulose  contants  the ,six  wood species for  timber  estate  are suitable  as raw material  for pulp  and paper  industry.